Entorhinal theta-frequency input to the dentate gyrus trisynaptically evokes hippocampal CA1 LTP - Stepan, Jens; Dine, Julien; Fenzl, Thomas; Polta, Stephanie; von Wolff, Gregor; Wotjak, Carsten; Eder, Matthias (Frontiers in Neural Circuits, 2012)
There exists substantial evidence that some forms of explicit learning in mammals require long-term potentiation (LTP) at hippocampal CA3-CA1 synapses. While CA1 LTP has been well characterized at the monosynaptic level, it still remains unclear how the afferent systems to the hippocampus can initiate formation of this neuroplastic phenomenon. Using voltage-sensitive dye imaging in a mouse brain slice preparation, we show that evoked entorhinal cortical (EC) theta-frequency input to the dentate gyrus highly effectively generates waves of neuronal activity which propagate through the entire trisynaptic circuit of the hippocampus (‘HTC-Waves’). This flow of activity, which we also demonstrate in vivo, critically depends on frequency facilitation of mossy fiber to CA3 synaptic transmission. The HTC-Waves are rapidly boosted by the cognitive enhancer caffeine (5 µM) and the stress hormone corticosterone (100 nM). They precisely follow the rhythm of the EC input, involve high-frequency firing (>100 Hz) of CA3 pyramidal neurons, and induce NMDA receptor-dependent CA1 LTP within a few seconds. Our study provides the first experimental evidence that synchronous theta-rhythmical spiking of EC stellate cells, as occurring during EC theta oscillations, has the capacity to drive induction of CA1 LTP via the hippocampal trisynaptic pathway. Moreover, we present data pointing to a basic filter mechanism of the hippocampus regarding EC inputs and describe a methodology to reveal alterations in the ‘input-output relationship’ of the hippocampal trisynaptic circuit.